2023
DOI: 10.1371/journal.pgen.1010947
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide circadian gating of a cold temperature response in bread wheat

Calum A. Graham,
Pirita Paajanen,
Keith J. Edwards
et al.

Abstract: Circadian rhythms coordinate the responses of organisms to their daily fluctuating environments, by establishing a temporal program of gene expression. This schedules aspects of metabolism, physiology, development and behaviour according to the time of day. Circadian regulation in plants is extremely pervasive, and is important because it underpins both productivity and seasonal reproduction. Circadian regulation extends to the control of environmental responses through a regulatory process known as circadian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 97 publications
0
2
0
Order By: Relevance
“…Among CCA1 and LHY targets, evening-expressed genes are highly enriched, and many of them contain EE motifs; however, CCA1 and LHY can also target morning-expressed genes or arrhythmic genes ( 45 ) ABF3 , featuring an oscillating pattern with a peak in the morning, falls in the category of CCA1/LHY targeted morning-expressed genes. Circadian clock can gate cold responses in Arabidopsis and bread wheat ( 41 , 54 ), specifically low-temperature induction of CBF1, 2, and 3 is gated by the circadian clock in Arabidopsis ( 54 ). Here, we demonstrate that the stress-induction of ABF3 differs at ZT1 and ZT10, suggesting the circadian clock may gate the stress responsiveness of ABF3 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among CCA1 and LHY targets, evening-expressed genes are highly enriched, and many of them contain EE motifs; however, CCA1 and LHY can also target morning-expressed genes or arrhythmic genes ( 45 ) ABF3 , featuring an oscillating pattern with a peak in the morning, falls in the category of CCA1/LHY targeted morning-expressed genes. Circadian clock can gate cold responses in Arabidopsis and bread wheat ( 41 , 54 ), specifically low-temperature induction of CBF1, 2, and 3 is gated by the circadian clock in Arabidopsis ( 54 ). Here, we demonstrate that the stress-induction of ABF3 differs at ZT1 and ZT10, suggesting the circadian clock may gate the stress responsiveness of ABF3 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies in crops also revealed the important role of the circadian clock in regulating stress responses. The circadian clock can gate genome-wide cold responses in bread wheat ( 41 ). PRR homologous gene Ppd-H1 in barley integrates drought stress signals to modulate spike development and flowering time ( 42 ).…”
mentioning
confidence: 99%